A Thermodynamic Approach for Selection of Anodizing Electrolytes in Aluminium‐Holmium System. Issue 6 (27th January 2020) - Shahzad, Khurram; Mardare, Cezarina Cela; Mardare, Andrei Ionut; Hassel, Achim Walter
Abstract: In this paper, an approach is described for the electrolyte selection to grow optimally anodic films on thermally co‐evaporated aluminium and holmium combinatorial alloys. This method based on thermodynamic and electrochemical principles proves that electrolyte selection for anodizing of alloys having different microstructures and electrochemical behaviour of individual constituents can be decided by superimposing potential‐ pH diagrams of individual constituents of the alloy. For the application of this approach, the most widely investigated valve metal, aluminium, and a non‐valve metal rare earth, holmium, have been chosen as a model case. Based on self‐constructed Eh‐pH diagrams and solubility data, suitable electrolytes and pH range leading to the formation of barrier‐type anodic films on aluminium and holmium as well as on their alloys are proposed. Abstract : The superimposition approach : Prediction of pH range and electrolyte selection for anodizing multi‐element systems having widely varying composition and inherent microstructure is a very challenging and time‐consuming task. Herein, a thermodynamic approach is presented based on systemic simulation and superimposition of Eh‐pH diagrams to rapidly identify the pH range and electrolytes for metallic alloys anodizing. The applicability of this approach is verified on two metals and their selected alloys having different compositions and microstructures using voltammetry, EIS, and corrosion studies.